Alteraciones anatómicas frecuentes de la cavidad nasal observadas en tomografía y su relación con sinusitis en niños entre 2 y 12 años atendidos en el hospital Manuel Ygnacio Monteros. - Tacuri Benavides, Nadia Krupscaya (2014)
The most common ANATOMIC ABNORMALITIES of the nasal cavity in children aged 2-12 years with rinusinusitis were determined to make this descriptive investigation with a sample represented by 70 patients with inflammatory sinus disease , who were a computerized tomography , was grouped as many patients in the group of 11 to 12 years, 49 % were female and 51 % were male , the most frequent anatomical variants were those that involved the middle turbinate , particularly hypertrophy , pneumatization (Concha Bullosa ) and paradoxical curvature, deviation of the nasal septum was found in 55 of the patients ( 79%); and , the presence of cells Agger nasi , 11.7% instead Haller cells were found in 6% of the same . In regard to the osteomeatal complex , 27 patients with secondary obstruction there of identified in full maxillary ostium obstruction disorders exacerbated by semilunar hiatus and uncinate process , it was determined that the enlarged lymphatic tissue was in 51 of patients and 59% in the moderate predominance . Given the variability of osteomeatal complex structures in the complete evaluation of the paranasal sinuses, it is important to consider the anatomic landmarks , so tomographic evaluation of them is the study of choice for patients with chronic rinusinusitis allowing decide timely treatment either the conservative or invasive , providing the attending physician, a more realistic view of the anatomy of the sinus area and providing details of the anatomical landmarks. . Keywords : Complex osteomeatal , CT , Paranasal sinuses .